Major shifts in gut microbiota during development and its relationship to growth in ostriches. Issue 10 (11th May 2019) - Videvall, Elin; Song, Se Jin; Bensch, Hanna M.; Strandh, Maria; Engelbrecht, Anel; Serfontein, Naomi; Hellgren, Olof; Olivier, Adriaan; Cloete, Schalk; Knight, Rob; Cornwallis, Charlie K.
Abstract: The development of gut microbiota during ontogeny is emerging as an important process influencing physiology, immunity and fitness in vertebrates. However, knowledge of how bacteria colonize the juvenile gut, how this is influenced by changes in the diversity of gut bacteria and to what extent this influences host fitness, particularly in nonmodel organisms, is lacking. Here we used 16S rRNA gene sequencing to describe the successional development of the faecal microbiome in ostriches ( Struthio camelus, n = 66, repeatedly sampled) over the first 3 months of life and its relationship to growth. We found a gradual increase in microbial diversity with age that involved multiple colonization and extinction events and a major taxonomic shift in bacteria that coincided with the cessation of yolk absorption. Comparisons with the microbiota of adults ( n = 5) revealed that the chicks became more similar in their microbial diversity and composition to adults as they aged. There was a five‐fold difference in juvenile growth during development, and growth during the first week of age was strongly positively correlated with the abundance of the genus Bacteroides and negatively correlated with Akkermansia. After the first week, the abundances of six phylogenetically diverse families (Peptococcaceae, S24‐7, Verrucomicrobiae, Anaeroplasmataceae, Streptococcaceae, Methanobacteriaceae) were associated with subsequent reductions in chick growth in an age‐specific and transient manner. These results have broad implications for our understanding of the development of gut microbiota and its associations with animal growth.